2021
DOI: 10.9744/jmk.23.1.27-39
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Packaging Color Scheme on Perceptions, Product Preferences, Product Trial, and Purchase Intention

Abstract: This study aims to understand the effect of different color scheme in perceptions and food product preference, product trial, and purchase intention. Using quantitative approach, the questionnaires data were cross tested by chi square and one-way ANOVA. The study found there were no significant differences between the price perception, the perceived quality, product preferences, product trial and intense to buy in the different color schemes, except white dominant color in perceived quality aspect. Respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Although people often assume the product's appearance, taste, and flavour when seeing packaging (e.g., photo and information), sometimes the point‐of‐sale communication impacts the customer's desire to purchase. However, different individuals respond to packaging designs differently 22 . In this study, the question ‘When thinking about a plant‐based hamburger, what sensations or expectations does this product convey to you?’ was answered, and Table 1 presents the results about dimensions, categories, number of words, and mention frequency, according to WA methodology.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although people often assume the product's appearance, taste, and flavour when seeing packaging (e.g., photo and information), sometimes the point‐of‐sale communication impacts the customer's desire to purchase. However, different individuals respond to packaging designs differently 22 . In this study, the question ‘When thinking about a plant‐based hamburger, what sensations or expectations does this product convey to you?’ was answered, and Table 1 presents the results about dimensions, categories, number of words, and mention frequency, according to WA methodology.…”
Section: Resultsmentioning
confidence: 93%
“…20 Although 89% of volunteers have carnivore or flexitarian habits, approximately 83% of interviewees are interested in consuming PBH and incorporating this type of food product into their diets. In a recent study, Basso et al 21 concluded that the vegetarian or vegan public do not enjoy buying PBH with aspect similar to conventional hamburgers. In the current research was constated that most of the volunteers which are not interested in PBH have vegetarian and vegan diet types.…”
Section: Participantsmentioning
confidence: 99%
“…This conclusion is supported by some of the background information offered previously. The packaging of the product will encourage consumers to acquire the things being marketed or offered, hence facilitating sales (Swasty et al, 2021). The author acknowledges the importance of package design and desires to contribute to the community by designing the packaging for rice box Alms and Friday Blessings of the Griya Sodaqo Indonesia Foundation.…”
Section: Yayasan Griya Sodaqo Indonesiamentioning
confidence: 99%
“…Dalam penjualan online selain harga, desain kemasan menjadi wajah utama untuk menarik konsumen. Desain kemasan yang unik dan menarik akan mempengaruhi persepsi konsumen pada produk tersebut; dan juga memberi kemungkinan membeli produk tersebut terlepas dari merek yang sudah terkenal ataupun tidak [5], [6]. Tiga aspek yang akan meningkatkan nilai dan popularitas produk makanan oleh-oleh adalah elemen sensorik, aspek kegunaan, dan makna simbolik.…”
Section: Pendahuluanunclassified